Designed loose nanofiltration membrane for efficient separation of low molecular dye/salt. Issue 31 (8th June 2022) - Jin, Jinbo; Du, Xilan; Yang, Jingkui; Li, Keda; Li, Jian; Qin, Shuhao; Yu, Jie; He, Min
Abstract: Efficient selective separation of low molecular weight dye/salt system is of great significance for promoting the development of membrane technology in the field of wastewater treatment. In this study, a loose nanofiltration membrane (LNF) was fabricated for the desalination of dye wastewater through a facile method. Firstly, styrene‐co‐maleic anhydride (SMA) containing anhydride group was added to PES membrane by blending, then polyethylene imide (PEI) was grafted onto the membrane surface by the reaction between amino group and anhydride group. Finally, the unreacted NH2 on the membrane surface were used for secondary cross‐linking with glutaraldehyde (GA) and ethylene glycol diglycidyl ether (EGDE) to obtain GA‐NF and EGDE‐NF membranes. Results showed that nanofiltration membranes with narrow pore size distribution and uniform structure are obtained. Compared with the aldehyde group in GA, the epoxy group in EGDE monomer has higher reactivity and hydrophilicity, which reacts with the amine group of PEI molecule to form hydrophilic hydroxyl group. Therefore, the water flux of EGDE‐NF membrane was about 20% higher than that of GA‐NF membrane, and the rejection of CR, AF, and EBT dyes was increased to more than 99%. Through chemical treatment of acid and alkali, both GA‐NF and EGDE‐NF membranes showed excellent separation performance stability. Abstract : Schematic diagram of nanofiltration membrane surface structure construction